High-resolution microendoscopy: a point-of-care diagnostic for cervical dysplasia in low-resource settings. Issue 1 (January 2017) - Grant, Benjamin D.; Fregnani, José H.T.G.; Possati Resende, Júlio C.; Scapulatempo-Neto, Cristovam; Matsushita, Graziela M.; Mauad, Edmundo C.; Quang, Timothy; Stoler, Mark H.; Castle, Philip E.; Schmeler, Kathleen M.; Richards-Kortum, Rebecca R.
Abstract : Cervical cancer is the third leading cause of cancer-related death among women in low-to-middle income countries. Pap testing and pathological services are difficult to implement under these settings. Alternative techniques for the diagnosis of cervical precancer in these settings are needed to reduce the burden of the disease. The objective of this study was to evaluate the diagnostic accuracy of a low-cost, high-resolution microendoscope imaging system in identifying precancerous lesions of the cervix in vivo . A retrospective study of 59 patients undergoing colposcopy for an abnormal Pap test was performed at Hospital de Câncer de Barretos in Brazil. All patients underwent colposcopy as per standard of care, and acetowhite lesions were recorded. High-resolution microendoscopy (HRME) images were obtained from one colposcopically normal region and from all lesions observed on colposcopy. Biopsies of abnormal areas were obtained and reviewed by three independent, blinded pathologists and compared with HRME findings. The mean nuclear area and the median nuclear eccentricity were calculated from HRME images acquired from each site. A diagnostic algorithm to distinguish histopathologically diagnosed cervical intraepithelial neoplasias of grade 2 or more severe lesions (high grade) from less severe lesions (low grade) was developed using these parameters. A test of trend was used to analyze the relationship between HRME positivity and severity of histopathogical diagnosis. Fisher's exact test was used to analyze differences in HRME positivity between high-grade and low-grade lesions. Evaluable images were obtained from 108 of 143 discrete sites. Of these, 71 sites were colposcopically normal or low grade according to histopathology and 37 were diagnosed as high grade on the basis of histopathology. Using the mean nuclear area and the median nuclear eccentricity, HRME images from 59 colposcopically abnormal sites were classified as high grade or low grade with 92% sensitivity and 77% specificity compared with histopathological findings. Increasing HRME positivity showed a significant trend with increasing severity of diagnosis ( P trend <0.001). We found a strong association ( P <0.001) between HRME positivity and a histopathological diagnosis of cervical intraepithelial neoplasia of grade 2 or higher. HRME demonstrated an accurate in-situ diagnosis of high-grade dysplasia. In low-resource settings in which colposcopy and histopathology services are severely limited or unavailable, HRME may provide a low-cost, accurate method for diagnosis of cervical precancer without the need for biopsy, allowing for a single 'screen-and-treat' approach.